IIUM engineering education a model - Shafie, Amir Akramin (American-Eurasian Network for Scientific Information, 2012)
Several reports and papers of the past decade suggesting paradigm shifts in engineering education are shown to reveal a common theme, engineering is an integrative process and thus engineering education, particularly at the baccalaureate level, should be designed toward that end. A change in intellectual culture, the roots of contemporary collegiate education currently are traced to their origin and attention is given to discussing the current emphasis on turning a course-focused education compared to a more holistic approach in which process and knowledge are woven throughout the curriculum. A system for baccalaureate engineering education is presented in terms of taxonomy of intellectual components connected holistically with a core focus on developing human potential, as opposed to the present system in which students are passed serially through course filters